(untitled) (Research, Society and Development, 2022)
Objective: to report the experience of medical students in the “Project Health in Territory”, through which they developed a strategy to combat smoking in Primary Health Care. Methodology: This is a descriptive study with a qualitative approach, an experience report about the development of a health strategy by the “Project Health in Territory” project in which family medicine tools were developed to identify the population profile of a territory in the city of Toledo, and proposed actions were described according to the local diagnosis. Results and discussion: the population profile demonstrated the demand for improvements in the treatment and prevention of smoking, thus, a longitudinal and four-step follow-up project was formulated for smoker users. Conclusion: The investigation of the population profile is essential for the development of applicable and effective health promotion strategies.